Mitigating Hypothetical Bias in Value of Time Studies: Lab-Experiment Results - Lars Hultkrantz; Xue Shengcong (Örebro University School of Business, 2010)
We present results from a series of willingness to-accept value-of-time choice experiments with students in Sweden and China, using both real and hypothetical purchases of the students time. Our results confirm negative hypothetical bias in stated choice elicitation of value-of-time. However, we find no evidence of hypothetical bias in a choice experiment where respondents to hypothetical or real offers have equal reference points (i.e., for purchase of their time "here and now"). Moreover, at least in the Chinese sample, we find that ex-post mitigation of negative hypothetical bias by certainty calibration, through recoding of uncertain "yes" responses into "no", overshoots, while calibration by restricting estimations to confident "yes" and "no" responses possibly performs better.
Keywords: C20; C91; D80; 330; Stated choice; Certainty calibration; Preference certainty